"Nobody Knows How You're Supposed to Interpret it:" End-user Perspectives on Prescription Drug Monitoring Program in Massachusetts. Issue 3 (May 2022) - Hong, Mina; Seymour, Sarah; Stopka, Thomas J.; Bandanza, Lane; Crocker, Erin; Morgan, Allison; Beletsky, Leo
Abstract : Objectives: America's overdose crisis spurred rapid expansion in the number and scope of prescription drug monitoring programs (PDMPs). As their public health impact remains contested, little is known about PDMP user experiences and perspectives. We explore perspectives of PDMP end-users in Massachusetts. Methods: Between 2016 and 2017, we conducted semi-structured qualitative interviews on overdose crisis dynamics and PDMP experiences with a purposive sample of 18 stakeholders (prescribers, pharmacists, law enforcement, and public health regulators). Recordings were transcribed and double-coded using a grounded hermeneutic approach. Results: Perspectives on prescription monitoring as an element of overdose crisis response differed across sectors, but narratives often critiqued PDMPs as poorly conceived to serve end-user needs. Respondents indicated that PDMP: (1) lacked clear orientation towards health promotion; (2) was not optimally configured or designed as a decision support tool, resulting in confusion over interpreting data to guide health care or law enforcement actions; and, (3) problematized communication and relationships between prescribers, pharmacists, and patients. Conclusions: User insights must inform design, programmatic, and policy reform to maximize PDMP benefits while minimizing harm.